The Influence Of Personality Factors And Attitude Towards Entrepreneurship On The Motivation To Start A Small Business Among Generation Y In Taiwan - Ng, Soo Hsien (2014)
The purpose of this research is to examine the influence of personality traits (Need for achievement, Risk taking, Tolerance for ambiguity, Locus of control and Self-efficacy) on the motivation generation y to start a small business in Taiwan. Additionally, attitude toward entrepreneurship has been explored as mediator factor in this study. The survey was conducted among 252 generation y who stay in the eight urban cities in Taiwan context. In essence, the research had built a framework based upon the Theory of Planner Behavior to entrepreneurship. Data collected was analyzed using SPSS and SmartPLS statistical tool. The results showed majority of the five personality trait dimensions were significantly related with motivation generation Y to start a small business Nevertheless, only three personality trait dimensions with attitude toward entrepreneurship were justified to mediator for the motivation of generation Y start a small business relationship, while self-efficacy and locus of control were not significant with mediator of attitude toward entrepreneurship. In summary, it is crucial for the Taiwanese, especially the generation Y in determinant of becoming self-employed to find testimony that not only the personality variables is important for determinants of motivation start a small business but attitude as mediator might be augment the relationship between the personality and motivation start-up a small business in Taiwan.